On Contractible J-Saces - Dawood, Narjis A.; Gasim, Suaad G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Jordan  curve  theorem  is  one  of  the  classical  theorems  of  mathematics, it states  the  following :  If    is a graph of  a  simple  closed curve  in  the complex plane the complement  of   is the union of  two regions,  being the common  boundary of the two regions. One of  the region   is  bounded and the other is unbounded. We introduced in this paper one of Jordan's theorem generalizations. A new type of space is discussed with some properties and new examples. This new space called Contractible -space.